Sistem Pakar Diagnosis Kelainan Sistem Pencernaan Pada Anak dengan Metode Dampster Shafer - Yuki Saputra; Sumijan; Abulwafa Muhammad (Universitas Putra Indonesia YPTK Padang, 2019)
The problems that often occur in children are as follows: Spit up, dysphagia, Cyclic vomiting syndrome, Colic, Diarrhea, Constipation. Dempster-Shafer is a mathematical theory for proof based on belief functions and plausible reasoning, which are used to combine separate pieces of information (evidence) to calculate the probability of an event. This theory was developed by Arthur P. Dempster and Glenn Shafer. In general the Dampster-Shafer theory is written in a Belief, Plausibility interval (Triara Puspitasari et al, 2016). Able to produce the type of disease experienced by the patient and provide recommendations for what treatment should be done by the patient.